Connecting social provisioning and functional finance in a post-Keynesian–Institutional analysis of the public sector - Zdravka Todorova (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
This paper establishes connections between the frameworks of social provisioning and functional finance, and discusses a post-Keynesian–Institutionalist theory of the public sector that emerges out of these linkages. The concept of social provisioning has emerged out of Institutional economics, and has been further developed by institutional and other heterodox economists. Its potential as a methodological foundation that connects various heterodox approaches has received some growing attention. Such discussions have not referred in an analytical manner to functional finance. On the other hand, the principles of functional finance have been elaborated and developed outside an explicit grounding in a social provisioning framework. The article specifies further the concept of social provisioning and discusses functional finance within such a framework. The framework of functional finance gains a structural and institutional grounding which enables a deeper and more critical conceptualization of the public sector.
Keywords: B52; E60; H60; P16; 330; social provisioning; functional finance; social classes